Oral health status of smokers and e-cigarette users: a longitudinal study - Ghazali, Aini Fatimah; Ismail, Ahmad Faisal; Daud, Azlina (2018)
Smoking is the most significant evitable cause of death and serious impairment in most developed countries. Recently, there has been a growing trend towards a new type of alternative device where cigarette smokers use traditional cigarettes with an electronic nicotine delivery system (ENDS) or electronic cigarettes (e-cigarettes) to receive nicotine. E-cigarettes have gained popularity after they were introduced in the market, especially among young adult smokers. Though the current government policy on nicotine control is being established to include e-cigarettes, at this point in history, e-cigarettes are almost entirely unregulated in Malaysia. To date, there is little documented evidence regarding the oral effects of e-cigarette use. Besides, the effect of cigarette smoking on health has been reported in numerous past studies including in Malaysia. However, the study findings of e-cigarette effect on oral health are unclear and scattered. Therefore, the aim of the study is to determine oral health of both e-cigarette and cigarette users at baseline and 6-month follow-up. A prospective longitudinal study was done on 45 cigarette users, e-cigarette users, non-smoking persons at the Specialist Clinic, Kulliyyah of Dentistry, IIUM Kuantan Campus. Oral health examination was conducted according to the World Health Organization (WHO) criteria. Dental caries was evaluated using the DMFT Index, while the periodontal parameters were assessed using plaque, gingivitis, gingival bleeding, and calculus indices. At baseline, the oral health status between smoking status showed the significant findings on Plaque Index (p=0.000), Gingival Index (p=0.000), and Gingival Bleeding Index (p=0.002). Meanwhile, at 6-month follow-up, the oral health status between smoking status showed significant findings on Plaque Index (p=0.000), Calculus Index (p=0.000), Gingival Index (p=0.003), and Gingival Bleeding Index (p=0.004). Moreover, the oral health status between smoking status at baseline and 6-month follow-up showed significant findings on Calculus Index for cigarette users (p=0.006); Gingival Index for e-cigarette users (p=0.003); and DMFT Index for cigarette users (p=0.005), e-cigarette users (p=0.000), and control group (p=0.025). The overall smoking status effect on oral health showed significant effect only on Calculus Index on cigarette users (p=0.005). In conclusion, both cigarette and e-cigarette have an impact on oral health. More research needs to be done to provide more evidence on the effects of e-cigarettes on health, specifically oral health, in a larger population and longer longitudinal study.